Social media design for dummies - Warner, Janine 1967- (Laura Ann); LaFontaine, David 1906-1998. 1947- (Sandra M.); 1957- (Margaret M.) (Hoboken, NJ John Wiley & Sons, Inc., 2014)
Take your social media site to the next level with a top-notch design! By using custom templates, you can create profiles for Facebook and YouTube; design a Twitter background or create a Google+ design; and even bring all your social media together on RebelMouse!
Includes index.
Keywords: Online social networks -- Design; Tin học